Типологія амфор культури шнурової кераміки Верхнього Придністер’я - Войтович, М.М. (Сіверщина в історії України, 2021)
Стаття присвячена типологічній характеристиці глиняних амфор культури шнурової кераміки (КШК) з території Верхнього Придністер’я. Типологічний поділ здійснений на основі класифікаційної схеми амфор, виконаних для території Південно-Східної Польщі Яном Махніком, яка актуальна
і для досліджуваних посудин із теренів українського Прикарпаття. Встановлено, що амфори походять із 27-ми поховань, із яких 19 мають повністю
збережений профіль. З огляду на форму та розміри, посудини розділені на
декілька типів. У процесі аналізу з’ясовано, що амфори типу А входять до
поховального інвентарю раннього етапу існування культури КШК. Амфори
типу І, ІІІ побутували в середньому етапі, тип ІІ, IV – на пізньому. Також
акцентовано увагу на тому, що максимального розповсюдження амфори як
вид посуду набрали на середньому етапі, натомість на пізньому вони кількісно поступаються кубкам. The article is devoted to the typological characteristics of clay amphorae
of Corded Ware culture from the territory of Upper Dnister region.
Typological division is made on the basis of classification scheme
of amphorae made for the territory of South-Eastern Poland by J. Machnik,
which is also relevant for examined ceramic ware from Ukrainian
Sub-Carpathian region. It is established that amphorae were collected
in 29 burials, 17 of them have a fully preserved profile. Depending
on the shape and size of ceramic ware they can be divided into several
types. Type A is represented by two finds (Kul’chytsi, barrow 7, 8)
up to 15 cm high with a convex squat body, wide bottom and cylindrical
neck ornamented with deepened horizontal grooves. Type I amphorae
(17 finds) prevail. They are characterized by a strongly convex
body with two massive eyelets located in the upper part of convexity or
on the line of maximum convexity of the body. Among ceramic ware of
type I there are amphorae of several forms (a–e) exist. Ceramic ware of
this type is mostly richly ornamented with a deep geometric motif (Krasiv,
barrow 2; Kolokolyn, barrow 1, 4; Bolekhivtsi, barrow 4; Koropuzh).
Amphorae of type II are usually unornamented. Four small ears placed
crosswise under the neck are the characteristic feature of ceramic ware.
Body of three products is strongly distended, with a well-defined bottom
and slightly sloping outward neck (Bovshiv; Balychi, barrow 7a;
Komarne). Body of tableware of type III is strongly convex, smoothly
turns into high funnel-shaped rims. Two small ribbon ears are placed
under the neck (Berezets, burials 1, 2). Type IV is represented by a single
egg-shaped find (Kul`chytsi, barrow 15). During analysis it was revealed
that amphorae of type A can be included in the burial inventory
of the early stage of CWC. Amphorae of type I, III existed at the middle
stage, type II, IV – at the later one. It is also emphasized that the
maximum distribution of amphorae as a type of ceramic ware falls on
the middle stage, while at the later stage they are quantitatively inferior
to the goblets.